Distribution and breeding biology of the lesser snow goose in central Arctic Canada - Ryder, John P (Wildfowl, 1971)
Distribution and aspects of the nesting biology of the Lesser Snow Goose Anser caerulescens caerulescens in central Arctic Canada are reported. Aerial surveys in 1965, 1966 and 1967 revealed 30 previously unrecorded nesting colonies. The total estimated nesting population in 1965 and 1967 was 8,299 Lesser Snow Geese. All the colonies were located on islands in shallow tundra lakes in the once inundated central lowland portion of the Arctic. It is suggested that food availability may be an important factor limiting goose distribution. Nesting studies at Karrak Lake (67 15' N., 100 15' W.) in 1966, 1967 and 1968 showed that the geese arrived in late May or early June and that nesting started about a week later. Clutch sizes in the three years were 4.2, 4.0 and 4.3 eggs. Data from 94 marked nests in 1968 showed that, on the average, successive eggs are laid every 1.3 days. Generally two or three eggs were laid then a day missed before completion. Incubation periods averaged 22.4 days, with a mode at 23 days. Incubation periods tended to decrease with increased clutch size. Over 60% of the marked clutches took less than a day to hatch. There was no relation between clutch size at hatching and the time taken to hatch. Nest and egg success was 86% and 69% respectively. About 40% of the goslings hatched from four-egg clutches. Most egg loss resulted from gull predation. Color ratios suggest that the blue-phase frequency (5% of 400 ringed geese) is lower than predicted (22%) from earlier studies in the central Arctic. Similar results in Baffin Island may reflect a general cooling trend in the Arctic. In view of an expected continued increase in nesting Lesser Snow Geese in the central Arctic and the importance of the area as the major nesting grounds of the relatively scarce Ross's Goose Anser rossii, studies are needed to determine the relationship between the two species during the nesting season.